IMPLEMENTASI GOOGLE CLASSROOM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID-19 - Alfurqan; Nur Khofifah Hasibuan (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2022)
One of the learning applications that is effectively used in online and offline conditions as it is today is Google Classroom, the purpose of this research is to find out the use, advantages and disadvantages and how to overcome the shortcomings of Google Classroom in learning Islamic religious education and character. This study uses a qualitative method with a descriptive approach. This research was conducted in class 10. E1 of SMAN 7 Padang with a total of 37 students consisting of 21 boys and 16 girls using research methods in the form of observation, interviews and documentation. The results show that the use of Google Classroom in the subject of Islamic religious education and character is very beneficial, especially for teachers and students, student learning outcomes increase, especially in understanding using technology as a learning medium. The most dominant deficiency was found in several cases of students being lazy in doing assignments, while the advantages were many, saving time, paper and cell phone memory storage. Many teachers describe Google Classroom as a complete learning medium that can contain student absences, materials and assignments. So it can be concluded that the use of Google Classroom as a learning medium is very effective, especially at the high school level.